Tujuan Beribadah: Suatu Kajian Pengalaman Ibadah Maria dari Betani Berdasarkan Yohanes 12:1-12 - Siang, Jhoni Lagun; Hutagalung, Stimson; Sagala, Rudolf Weindra; Ferinia, Rolyana (Tumou Tou, 2023)
The purpose of this study was to determine the purpose of worship based on John 12:1-12. The method used in this article is literary research or literature with a descriptive approach. As Christians the purpose of our worship is to glorify God's name, God-centered worship should be where God is glorified, regardless of the human factor. The purpose of worship is not only to receive blessings from God, but also to give offerings to God.